Edible oil nanoemulsion: An organic nanoantibiotic as a potential biomolecule delivery vehicle. Issue 7 (3rd May 2018) - Saxena, Varun; Hasan, Abshar; Sharma, Swati; Pandey, Lalit M.
ABSTRACT: Water-insoluble bioactive compounds typically require the formulation of lipophilic, antimicrobial delivery system to enhance their bio accessibility. Edible delivery system, in this contrast, plays an important role in food and medical industry. In the present study, an attempt has been made to increase the bioavailability of a model bioactive compound α-tocopherol as a food supplement through edible (coconut) oil nanoemulsion. A 9.5 mg mL −1 of encapsulation capacity was obtained with almost 100% release of the loaded α-tocopherol within 24 h. The nanoemulsions were analyzed for various physical and chemical stability parameters, namely, solvent, ionic concentration, temperature, rotatory motion, and various gastrointestinal pH zones. The prepared nanoemulsions were found stable to these parameters. The synthesized nanoemulsions were also evaluated for their biocompatibility and antimicrobial activity. The result showed reasonable cell viability (biocompatibility) with apposite antimicrobial activity confirming the synthesized nanoemulsion as a potential delivery vehicle. Experimental release data were fitted by combining a diffusion-controlled (Higuchi model) and a kinetic-controlled (first-order kinetics) models. The contribution of kinetic-controlled release was found about 70% and that of diffusion-controlled release was found about 30%. The present study reveals plausible application of edible oil nanoemulsion in food, beverages, and health care industries. GRAPHICAL ABSTRACT: